Cochlear implant outcomes in patients with Meniere's disease: a large case series. (2nd November 2022) - Kanona, Hala; Forde, Cillian; Van Rooyen, Anne M.; Keating, Peter; Bradley, Jane; Pendolino, Alfonso Luca; Mehta, Nishchay; Manjaly, Joseph G.; Khalil, Sherif; Lavy, Jeremy; Saeed, Shakeel R.; Shaida, Azhar
Abstract : Objective: To perform a matched cohort study to assess whether patients with Meniere's Disease (MD) require more intensive auditory rehabilitation following cochlear implantation (CI) and identify factors that may affect outcomes in patients with MD. Methods: A retrospective case review was performed. MD and control patients were matched for age, biological sex, implant manufacturer and electrode design. Outcomes measured were speech scores, number of visits to audiology department following switch-on, and post-operative active MD. Results: Forty consecutive implanted MD patients were identified between May 1993 and May 2019. Patients with active MD following CI required significantly more visits to the audiology department compared to controls (P < 0.01) and patients who had inactive MD post-operatively (P < 0.01). However, in MD patients, active MD was less likely following CI (P = 0.03). In patients who continued to experience active MD post-operatively, further medical and surgical ablative intervention was required to control ongoing Meniere's attacks. Conclusion: We present the largest case series of performance outcomes in CI patients with MD. Although speech outcomes in MD patients are comparable to controls, patients with active MD pre-operatively are more likely to experience variation in CI performance requiring a prolonged period of auditory rehabilitation compared to inactive preoperative MD.